Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3847/1538-4357/abe1b1
|View full text |Cite
|
Sign up to set email alerts
|

Brought to Light. II. Revealing the Origins of Cloaked Spiral Features in Cluster Passive Dwarf Galaxies

Abstract: In our companion paper (Brought to Light I: Michea et al.), we reveal spectacular spiral-galaxy-like features in deep optical imaging of nine Virgo early-type dwarf galaxies, hidden beneath a dominating smooth stellar disk. Using a new combination of approaches, we find that bar- and spiral-like features contribute 2.2%–6.4% of the total flux within 2 R eff. In this study, we conduct high-resolution simulations of cluster harassment of passive dwarf galaxies. Following close pericenter passag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Simulations have shown that in this case, the features are expected to be fairly symmetrical for high speed encounters, rather asymmetrical in case of low speed encounters (like M51) (Byrd & Valtonen 1990). In the latter case, the galaxy appearance could be similar to ram pressure stripped cases, but the nearby companion should be still visible, allowing us to distinguish between the two mechanisms (Smith et al 2021).…”
Section: Discussionmentioning
confidence: 90%
“…Simulations have shown that in this case, the features are expected to be fairly symmetrical for high speed encounters, rather asymmetrical in case of low speed encounters (like M51) (Byrd & Valtonen 1990). In the latter case, the galaxy appearance could be similar to ram pressure stripped cases, but the nearby companion should be still visible, allowing us to distinguish between the two mechanisms (Smith et al 2021).…”
Section: Discussionmentioning
confidence: 90%
“…In the second paper of this series (Brought to Light II, Smith et al 2021) we simulated dwarf ETGs along different orbits in a Virgo-like cluster potential. We found that tidal triggering can reproduce the disk substructures observed in Virgo dwarf ETGs only when a galaxy contains a cold and thin disk embedded in a more massive and hot disk, and experiences very plunging pericenter passages (r peri < 0.25 r vir ).…”
Section: Implications Of Substructure Morphologymentioning
confidence: 99%
“…In Brought to Light II (Smith et al 2021), we compared the morphology of these substructure features with those arising from high-resolution numerical simulations of tidal harassment by a galaxy cluster potential. We found that the formation of spiral arms and bars can be effectively tidally triggered, during close pericenter passages, in dwarf ETGs that contain a fraction of their stellar disk in a cold, highly rotationally-supported component embedded in a comparatively hotter, little rotationally-supported disk that dominates the total galaxy mass.…”
Section: Introductionmentioning
confidence: 99%
“…In "Brought to Light II" (Smith et al 2021), we compared the morphology of these substructure features with those arising from high-resolution numerical simulations of tidal harassment by a galaxy-cluster potential. We found that the formation of spiral arms and bars can be effectively tidally triggered, during close pericenter passages, in dwarf ETGs that contain a fraction of their stellar disk in a cold, highly rotationally supported component embedded in a comparatively hotter, lesser rotationally supported disk that dominates the total galaxy mass.…”
Section: Introductionmentioning
confidence: 99%